Pain After Spine Fusion for Adolescent Idiopathic Scoliosis: Current Concept Review - Younis, Manaf H.; Haydel, Adam L.; Saunee, Lauren; Clement, Rutledge C. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Surgical correction of spinal deformity has shown good results in terms of pain reduction, but it is uncertain why some patients continue to have chronic pain following surgery. With the true prevalence and etiology of chronic back pain following posterior spinal fusion with instrumentation (PSF) for Adolescent idiopathic scoliosis (AIS) unknown, we sought to review the prevalence and potential causes of chronic back pain following PSF for AIS. After a thorough literature review, the true prevalence of chronic pain following surgery remains difficult to quantify. Definitions of chronic pain include severe pain within 6 months of surgery, pain at least one time in the two years following surgery, “persistent pain,” moderate to severe pain two years post-operatively, pain in the five years following surgery defined as often or very often, and many more. Given the lack of a cohesive definition, true prevalence of chronic pain remains unknown but ranged in previous studies from 16%-64.4% two years post-operatively. Many patients did not have an obvious etiology of pain identified. Potential causes included mechanical back pain, adjacent segment disease, pseudoarthrosis, implant-related failures, infection, and Proximal junctional failure. Common risk factors for these causes of chronic pain include high pre-operative pain levels and the degree and type of curve pre-operatively.